Enactment of HBMMC five-level inverter based D-STATCOM using robust controllers - Ramakrishna, Elluru; Jayakrishna, Gadhamappagari; Peddakotla, Sujatha (International Journal of Power Electronics and Drive Systems (IJPEDS), 2024)
This paper provides the results of a concerted investigation into developing a robust voltage controller for the modular multilevel converter (MMC) used in the D-STATCOM. The simplicity of the half bridge (HB) sub-module, along with the fact that it has minimal conduction losses, led to its adoption in the MMC. For the purpose of controlling the HB MMC switches, an enhanced modulation strategy based on the phase disposition (PD) scheme has been implemented. In the presence of nonlinear load conditions, the converters are experiencing difficulties with the DC voltage balancing. The sliding mode controller (SMC) is utilized so that the DC voltage can be maintained in a balanced state. Performance characteristics including active power, reactive power, dc voltage control and THD are shown and compared. For the purpose of simulating the indicated methodology, MATLAB/Simulink is the tool of choice.